Successful management of critical iliac artery aneurysm which is unexpectedly accompanied by acute aortic dissection type B: A case report. Issue 11 (12th September 2018) - Alirezaei, Toktam; Mozafar, Mohamad
Key Clinical Message: Acute aortic dissection with concurrent large aortic aneurysm is a catastrophic condition. Clinicians may be faced with the dilemma of how to manage these patients. This case reports a successful management crisis in a patient with a type B aortic dissection and a large left common iliac artery aneurysm. Abstract : Acute aortic dissection with concurrent large aortic aneurysm is a catastrophic condition. Clinicians may be faced with the dilemma of how to manage these patients. This case reports a successful management crisis in a patient with a type B aortic dissection and a large left common iliac artery aneurysm.